PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENUNJANG PELAKSANAAN KURIKULUM 2013 PADA MATA PELAJARAN KIMIA SMA POKOK BAHASAN REAKSI REDUKSI OKSIDASI DAN TATA NAMA SENYAWA - Retno Eko Rifkowati; Betty Holiwarni; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to develop a student worksheet based on problem based learning on reduction and oxidation reaction subject in the Chemistry Education Study Program. The result of this research and development is student worksheet product which can be used by students in the process of learning. The method used in this research consists of 4 development stages namely define, design, develop, and disseminate or adapted into 4-P Method, which is pendefinisian, perancangan, pengembangan, dan penyebaran. The development model is modified by the researchers only until the development stage. Recapitulation of the average score of the assessment of the four aspects of student worksheet by the validator team, content, language, presentation, and successive graphics have 89.16%, 91.67%, 90%, and 89.56%. Thus, the overall average score of student worksheet validation the oxidation-based reduction reaction based on Problem Based Learning is 89.59%. Based on the eligibility criteria of learning tools in Riduwan (2012), the criteria of 89.59% analysis included in valid category.Keywords : Student worksheet, Problem Based Learning, Reduction and Oxidation Reaction.